Sapu pada Kacang Hias (Arachis pintoi): Penyakit Baru yang Berasosiasi dengan Fitoplasma - Budiyarto .; Kikin Hamzah Mutaqin (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Pinto peanut (Arachis pintoi) witches’ broom is a new disease found in Bogor at high incidence and has not yet been reported elsewhere. Symptom type of the disease is very similar to that of peanut (A. hypogea) witches’ broom, which has been well known to be associated with phytoplasma. Both A. pintoi and A. hypogea witches’ broom causal agent are transmissible to both healthy A. pintoi or A. hypogea, with grafting or vector transmission using peanut witches’ broom phytoplasma specific vector, Orosius argentatus. All combination of transmission means resulted in an identical type of witches’ broom symptom. Further confirmation using polymerase chain reaction detection and identification of phytoplasma employing universal primer pair for phytoplasmas (P1/P7), showed that all of the diseased plants, either from field or transmitted plants is associated with phytoplasma. The A. pintoi witches’ broom phytoplasma is likely identical to that of A. hypogea.Key words: Arachis pintoi, Orosius argentatus, phytoplasma, witches’ broom